Mosaicism in Tuberous Sclerosis Complex - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Six families with mosaicism in a series of 62 unrelated families with a mutation in one of the two tuberous sclerosis complex (TSC) genes, TSC1 or TSC2, are reported from the Erasmus University and Hospital, Rotterdam, The Netherlands.